Perceived stress and life satisfaction among elderly migrants in China: A moderated mediation model - Hou, Yanjie; Yan, Shiyuan; Zhang, Lin; Wang, Hao; Deng, Ruyue; Zhang, Wenjing; Yao, Jun (Frontiers in Psychology, 2022)
Objective: Our study aims to test whether anxiety mediated the association between perceived stress and life satisfaction and whether the mediating effect was moderated by resilience among elderly migrants in China. Method: We used self-reported data collected from 654 elderly migrants in Nanjing. Regression analyses using bootstrapping methods were conducted to explore the mediating and moderating effects. Results: The results showed that anxiety mediated the relationship between perceived stress and life satisfaction(indirect effect=-0.040, CI[-0.066,-0.017]). Moreover, moderated mediated analysis indicated that resilience moderated the path between anxiety and life satisfaction(moderating effect=0.034, 95% CI [0.021,0.048]). In particular, anxiety had a negative impact on life satisfaction only for Chinese elderly migrants with lower resilience. Conclusion: Our study suggests that perceived stress could reduce life satisfaction among elderly migrants as their anxiety levels increase. Fortunately, elderly migrants’ resilience could undermine this negative effect.